'These enchanted hills': transforming cultural landscapes in the Hills Face Zone, South Australia. (16th November 2020) - Smith, Pamela A.; Pate, F. Donald; Piddock, Susan
ABSTRACT: Tensions between constructions of nature and culture are increasingly relevant in the twenty-first century as natural environments near large population centres come under increasing pressure from developers. The western face of the Mount Lofty Ranges, South Australia, is a historically significant cultural landscape where, following European colonisation, landscape use transitioned between 'cultural' and 'natural' according to local economies and changing public perceptions. Historical and archaeological evidence for the evolution of this landscape illustrate the dichotomies between these changing landscape values and growing public appreciation of the aesthetic qualities of this 'green' backdrop to the city of Adelaide. During the 1960s and 1970s the South Australian Parliament passed legislation creating a Hills Face Zone to protect this region from urban development. This paper presents evidence why, fifty years later, this model for landscape management is increasingly relevant as world population growth and urban sprawl extend into natural environments.